Real time simulation of sensorless control based on back-EMF of PMSM on RT-Lab/ARTEMIS real-time digital simulator - Abdelhakim Idir; A. Ahriche; K. Khettab; Y. Bensafia; M. Kidouche (Institute of Advanced Engineering and Science, 2019)
Real-time simulation (RT) is very useful for rapid prototyping of complex and expensive systems using the high performance of a multiprocessor system. It has many applications in the field of testing controllers and protection systems under real conditions. In this article, Real-time simulations results of sensorless control of permanent magnet synchronous motor (PMSM) are presented. This simulator consists of two major subsystems, software with a Matlab / Simulink and hardware including FPGA boards for data acquisition, control boards and sensors. The two subsystems were coordinated together to achieve the simulation RT. To estimate the rotor position, a sliding mode observer (SMO) based on back emfs of the motor was implemented. The stability of the proposed method was verified using the concept of Lyapunov. A real-time system based on FPGA, is used for implementing and testing the algorithm for rotor position estimation based on back-emf tracking.